Plan estratégico y su relación con el desarrollo empresarial del área solupack de la empresa reyleche, parroquia Patricia Pilar, cantón Buena Fe, período 2014 – 2018 - Delgado Campuzano, Johana Margarita (2015)
This research project was conducted in Patricia Pilar Parish in order to determine a strategic plan for the area Solupack and thus develop structured problems by developing the strategic plan for business development with the aim of making the SWOT matrix identify strategies for good management decisions for the development of the strategic plan. This research was conducted with the determination of a strategic plan for the area Solupack and decision-making of the company in order to carry out the strategies and get the mission and vision. By hypothesis has been obtained contains that will impact the decisions that are feasible for business development area, strategies for good management in the organization and planning objectives. This grouping of data Ricardo Holly applying the interview was conducted the manager Eng. Which are 13 questions and a survey administrative staff consisting of 8 questions since it was observed that it is important that a strategic plan is conducted Solupack in area.